National Income and Expenditure 2011 - Ireland. Central Statistical Office (CSO). (Dublin: Stationery Office, 2012)
This report includes preliminary estimates of the national accounts for the year 2011 together with revised estimates for the years 2006 to 2010. The tables relate to national income and expenditure, capital formation and savings together with details of transactions of the government sector classified in accordance with national accounting definitions.
Keywords: National Income and Expenditure -- Ireland; Capital Formation -- Ireland; National Accounts -- Ireland